France : Report on the Observance of Standards and Codes-Transparency in Monetary and Financial Policies; An Update. (IMF Staff Country Reports; Country Report ;, 2001)
This note provides a report on the Observance of Standards and Codes in France, and provides updates on the transparency in monetary and financial policies. The framework for supervision and regulation applicable to a specific group of mutual insurance firms has been modified by adjusting the law governing these institutions to comply with European regulations concerning insurance. Once implementing regulations are in effect, these insurance companies will need to meet the same solvency rules as provided in the insurance code.